Strategic Development Challenges in Marine Tourism in Nunavut - Margaret E. Johnston; Jackie Dawson; Patrick T. Maher (Resources, 2017)
Marine tourism in Arctic Canada has grown substantially since 2005. Though there are social, economic and cultural opportunities associated with industry growth, climate change and a range of environmental risks and other problems present significant management challenges. This paper describes the growth in cruise tourism and pleasure craft travel in Canada’s Nunavut Territory and then outlines issues and concerns related to existing management of both cruise and pleasure craft tourism. Strengths and areas for improvement are identified and recommendations for enhancing the cruise and pleasure craft governance regimes through strategic management are provided. Key strategic approaches discussed are: (1) streamlining the regulatory framework; (2) improving marine tourism data collection and analysis for decision-making; and (3) developing site guidelines and behaviour guidelines.